Titanium particles induce apoptosis by promoting autophagy in macrophages via the PI3K/Akt signaling pathway. Issue 9 (8th June 2020) - Xian, Guoyan; Chen, Weishen; Gu, Minghui; Ye, Yongyu; Yang, Guangpu; Lai, Weiming; Xiao, Yinbo; Zhao, Xiaoyi; Zheng, Linli; Pan, Baiqi; Kang, Yunze; Zhang, Ziji; et al.
Abstract: Chronic inflammation and infection in the tissue surrounding implants after total joint replacement is closely associated with the innate immune response to surgical implants. Wear particles are known to increase apoptosis and impair the innate immunity in macrophages, which can cause immunosuppression around the implants. Excessive autophagy can induce apoptosis. However, the link between autophagy and apoptosis in macrophages during chronic inflammation and infection remains unknown. In this study, we investigated the autophagy and apoptosis induced by titanium particles in RAW264.7 macrophages, and in the interface membrane of patients with late‐onset periprosthetic joint infection (PJI). We found that titanium particles stimulated autophagy and apoptosis in macrophages. Inhibition of autophagy significantly reduced titanium particle‐induced apoptosis in macrophages, which may be related to the PI3K/Akt signaling pathway. The secretion of inflammatory factors, such as IL‐1β, IL‐6, and TNF‐α, decreased after inhibition of autophagy in titanium particle‐stimulated macrophages, which may be caused by immune dysfunction due to titanium particle‐induced autophagy and apoptosis in macrophages. Furthermore, our in vivo mouse calvarial model also showed that autophagy inhibitors lowered the rate of cell apoptosis. Our findings indicate that wear particle‐induced apoptosis may be caused by enhanced autophagy in macrophages, which could potentially impair the local innate immunity in periprosthetic tissues and could be a risk factor for PJI. Based on these results, autophagy modulators may act as a new therapeutic option for PJI.